Comparison between Direct Laryngoscopy with and without Aerosol Box for Intubation in Patients undergoing General Anaesthesia during COVID-19 Pandemic- A Randomised Controlled Study - Krupa P Patel; Ashish P Jain; Vaidehi J Mehta; Hetal A Parikh; Chinar N Patel (Journal of Clinical and Diagnostic Research, 2022)
Introduction: The airway management of patients with COVID-19 is a high risk task for anaesthesiologists. Several innovations have been born as a result of this problem, including aerosol boxes and clear plastic sheets. Aim: To compare the timing and attempt of direct laryngoscopy with and without aerosol box for intubation in patients undergoing general anaesthesia during the COVID-19 pandemic. Materials and Methods: This was a randomised controlled study was conducted in Parul Sevashram Hospital, Parul University, Vadodara, Gujrat, India from April 2021 to September 2021. A total of 50 patients were randomly divided into two equal groups as group A was intubated with an aerosol box and a macintosh laryngoscope, while group B was intubated with a clear plastic sheet and macintosh laryngoscope. With proper airway precautions and Personal Protective Equipments (PPE) comparative assessment of patients undergoing surgery in general anaesthesia was done. Time to intubate, number of attempts, ease of Endotracheal Tube (ETT) tube insertion, quality of Laryngoscopy view and Cormack Lehane scores were assessed in both the groups. Results: The mean time for intubation was high at 29.72 seconds in group A, while it was 23.16 seconds in group B; the difference was significant. Overall, 20 out of 25 (80%) patients could be intubated in 1st attempt in group B as compared to 15 out of 25 (60%) in group A. Airway visualisation using Percentage of Glottic Opening (POGO) scoring and Cormack Lehane staging were suggestive of better visualisation in group B than group A. Difficulties encountered during intubation like laryngoscopy, glottic visualisation, arm movement restriction, ETT negotiation, and stylet removal were lesser in group A as compared to group B. The incidence of complications like sore throat and airway bleeding were lower in group B as compared to group A. Conclusion: In the COVID-19 era, aerosol box and clear plastic sheets are effective barrier measures for airway management to prevent the anaesthesiologists from the aerosol transmission. But, airway management with clear plastic sheet is technically easier than aerosol box.